Effect of recombinant bovine somatotropin administration on milk production, composition and some hemato-biochemical parameters of lactating goats - Sallam S.M.A.; Nasser M.E.A.; Yousef M.I. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The objectives of the present study were to evaluate the effects of recombinant bovine somatotropin (rbST) on milk production, composition and some hemato-biochemical characteristics in Damascus goats. Fifteen Damascus lactating goats in their third to fourth lactation season and at 30-40 days postpartum were divided into three equal groups. The first group was served as control, while the second and third groups were injected, once every week for 8 weeks, with low (50 mg/doe) or high (100 mg/doe) doses of rbST, respectively. Supplementation with rbST resulted in a significant (P<0.05) increase in total milk yield by 24.3 and 22.5 % for 50 mg or 100 mg of rbST, respectively compared with control. Body weight and dry matter intake of does were not affected significantly by rbST treatment. While average daily gain (ADG) of kids that were suckling rbST-treated does was higher (11 and 10.5 % for low and high doses of rbST, respectively) than for kids of control does during the treatment period. Supplementation with rbST caused insignificant (P>0.05) increase in the levels of total solids, milk protein and fat as compared with control, while lactose significantly (P<0.05) increased. On the other hand, ash, haematological parameters, plasma proteins and the activities of plasma aspartate aminotransferase (AST), alanine aminotransferase (ALT), glutathione S-transferase (GST), alkaline phosphatase (AlP), acid phosphatase (AcP), and the levels of thiobarbituric acid-reactive substances (TBARS) and cholesterol were not affected by treatment. The results of the present study suggest that rbST is efficacious in increasing milk yield and kid growth up to 50 mg/14 d without adverse effects on lactating goats.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)